Il Tesoro della Lingua Italiana delle Origini - Squillacioti, Paolo (Verbum – Analecta Neolatina, 2002)
The Tesoro della Lingua Italiana delle Origini (TLIO) is the main project of the Institute of Italian Research Council ‘Opera del Vocabolario Italiano' (OVI). TLIO is a historical dictionary of Old Italian; its most important characteristic is that of having been founded on a huge database (around 19 million words in 1581 texts), consisting of texts written in any variety of mediaeval Italian and dated within 1375. The database is available in internet thanks to the international consortium ItalNet (http://www.italnet.nd.edu). The TLIO database not only allows the writing out of dictionary entries, but is also an autonomous tool, useful for the research on Old Italian.